Phenomenological Study of Women Entrepreneurs and Their Impact on Socio-Economic Growth in Malaysia - Juhary, Ali; Noraini, Ahmad (2023)
The study was conducted on women entrepreneurship and socio-economic growth in Malaysia. The study on women entrepreneurship in Malaysia was on Women entrepreneurship is said to be the emerging phenomenon of the 21th Century. It has been recognised that today women are as likely as men seeking business opportunities around them. Women entrepreneurs are able to contribute to socioeconomic development of the country. However, women entrepreneurs were found to encounter internal and external barriers to their business growth. Based on the literature review on entrepreneurship highlighted numerous constraints and barriers to women entrepreneurship which include amongst others gender-biased, lack of entrepreneurial and business skills, finance and even the personality characteristics of women. In this study there were four factors and barriers facing entrepreneurship growth were identified. They were personality traits, business skills, knowledge and training, the need for government support system and support systems that contribute to women entrepreneurship growth and the socio-economic growth of the country. In order to answer these four objectives, this study conducted a focus group method in order to clearly understand the phenomenon of women entrepreneurship in Malaysia. It has been informed the focus group approach is commonly used in social science research. A selected group of 10 key person women entrepreneurs answered the interview and discussion via online focus group discussion. The structured questionnaires were also distributed to the 10 entrepreneurs participated and responded in focus group discussion. The focus group discussion centred on four themes on women entrepreneurship development, women and its contribution to socio-economic growth, including household income, employment and society wellbeing. Data collection on entrepreneurial psychological factors, barriers to women entrepreneurship success and growth, government support systems and the social and economic growth of the country were gathered from the focus group discussion and were analysed using NVIVO software package. The results of the study were tabulated based on four themes and sub themes. In conclusion this research has established a woman entrepreneurship socio-economic model in Malaysia. A causal relationship model configured variables as a main guidance for entrepreneurship stakeholders and practitioners. This study was a phenomenological study on woman entrepreneurship and its effect on women socio-economic growth in Malaysia. The study provided implications to stakeholders in addressing women entrepreneurship problems and barrier to women business growth. It was recommended that further research on women entrepreneurship will be based on industrial and business sectors dominated by women.